Resource Allocation with Carrier Aggregation in Cellular Networks Optimality and Spectrum Sharing using C++ and MATLAB - Shajaiah, Haya (Springer International Publishing, 2018)
This book introduces an efficient resource management approach for future spectrum sharing systems. The book focuses on providing an optimal resource allocation framework based on carrier aggregation to allocate multiple carriers' resources efficiently among mobile users. Furthermore, it provides an optimal traffic dependent pricing mechanism that could be used by network providers to charge mobile users for the allocated resources. The book provides different resource allocation with carrier aggregation solutions, for different spectrum sharing scenarios, and compares them. The provided solutions consider the diverse quality of experience requirement of multiple applications running on the user's equipment since different applications require different application performance. In addition, the book addresses the resource allocation problem for spectrum sharing systems that require user discrimination when allocating the network resources.